Humanitarian and Conflict Oriented Early Warning: A Historical Background Sketch - Adelman, Howard (Refuge: Canada’s Journal on Refugees, 1997)
This article provides a brief and informative overview of the overall development of early warning over past years. It also includes references to the author’s own involvement in the field as Director of the Centre for Refugee Studies and, later, Director of the Prevention/ Early Warning Unit.